(3GdYdGeI GdJLGQjI ef efXhQESJgdGcj (B/s - (3eZQGhj, eMj GdOjf YHO GdbGOQs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2020)
(3age Sdhc GdeSJgdc hCfhGYg hGdYhGed GdeDKQI Ydjg, GdYdGeI hGdYdGbI eYg ef NdGd GdCSS GdfXQjI ddYdGeI GdJLGQjI h QhGHWgG, cPdc hbY GdYdGeI Ydi Sdhc GdeSJgdc GVGaI Gdi GdYhGed GdeSGgeI aj GNJjGQ gPg GdYdGeI eY ChLg JCKjQgG Ydi Sdhcg ef NdGd GdhYj hGdJUhQGJ GdGjLGHjI eY JZjjQ GdGJLGgGJ hJWhjQ GdKbI ChGdeNGWQI aj GdTQGA s
(3eQGLY U(B.163s
Keywords: (3GdGSJgdGcs; (3GdJShjbs; (3GdYdGeGJ GdJLGQjIs